Abundance and Ecology Index of Plankton in Island Seurudong Waters, South Aceh: Kelimpahan dan Indeks Ekologi Jenis Plankton di Perairan Pulau Seurudong, Aceh Selatan - Lubis, Friyuanita; Lisdayanti, Eka; Najmi, Nurul (Habitus Aquatica, 2023)
Plankton are organisms that live in the ocean water column and move with the currents. The plankton is divided into two types, namely phytoplankton and zooplankton. This study aims to determine the abundance anda ecologycal index of phytoplankton and zooplankton in the waters of Seurudong Island, South Aceh district. Water sampling with a volume of 100 liters was filtered using a plankton net at each station. There are 3 sampling locations. Each station has 4x repeats. Measurement of water quality is carried out simultaneously with water sampling to identify the type of plankton. The results of this study indicate that there are differences in abundance at each station. The abundance of phytoplankton at station 1 was 12520 cells/L, Station 2 was 5643 cells/L, and Station 3 was 3510 cells/L. The abundance of zooplankton at station 1 was 918 ind/L, station 2 was 1225 ind/L and station 3 was 1575 ind/L. Based on ecologycal index, phytoplankton and zooplankton  respectively showed H’ (0,97 – 1,05), C (1,0) dan E (0,26 – 0,33) while H’ (0,55 – 0,78), C (1,0) dan E (0,21 – 0,24). The composition of phytoplankton and zooplankton in these waters is closely related to the quality of the waters and food sources for other organisms.